A Fuzzy Logic Transportation Model for Optimizing Pharmaceutical Supply Chain in Iran - Zarrabi , Ferial; Hasanpour Jesri, Seyed Omid (Annals of Optimization With Applications, 2025)
The pharmaceutical industry in Iran plays a significant role in the nation’s economy. This sector's supply chain is made up of various players, including suppliers of chemicals and packaging materials, as well as retailers who market these products. The structure of this supply chain is quite extensive, encompassing production facilities, storage units, distributors, and wholesalers such as pharmacies, hospitals, and government purchasing centers, along with retailers spread across different regions. This research introduces a transportation strategy specifically for the pharmaceutical industry, with the goal of streamlining logistics operations. The proposed framework takes into account a variety of elements, decision-making variables, and constraints, reflecting the complex dynamics of drug supply networks. To evaluate how well the transportation model performs under uncertain conditions, fuzzy logic techniques are employed. The primary objective is to enhance operational efficiency, lower costs, and improve the overall effectiveness of logistics within the pharmaceutical sector. The results demonstrate the viability and success of the proposed approach in addressing the challenges related to managing transportation in the pharmaceutical field.